Vom Verteilen zum Gestalten Geschichte der betrieblichen Mitbestimmung in der westdeutschen Automobilindustrie nach 1945 - Owetschkin, Dimitrij (Forschung aus der Hans-Böckler-Stiftung, 2016)
Worker's councils between protectionist policies and policies of social transformation: a history of the industrial consultation processes in the West-German automobile industry after the Second World War.